Empowering Tourism Awareness Groups (Pokdarwis) through Biodiversity Education and Photography Training to Promote Conservation-Based Ecotourism in Singgalang Tandikek Nature Park - Atifah, Yusni; Putri, Dwi Hilda; Achyar, Afifatul; Chatri, Moralita; Violita, Violita; Pratama, Sandi Fransisco; Vauzia, Vauzia; Putri, Irma Leilani; Putri, Aulia Devani (Pelita Eksakta, 2025)
At the present time, pressures on local ecosystems put many endemic species at risk of extinction if conservation measures are not promptly implemented. This community service program aimed to empower tourism awareness groups (Pokdarwis) in Singgalang Tandikek Nature Park through biodiversity education and photography training to support conservation-based ecotourism. The program targeted local guides, providing knowledge on endemic and protected species, particularly the Sumatran striped rabbit (Nesolagus netscheri), combined with practical photography skills using smartphones and ethical documentation practices. Activities included biodiversity lectures, hands-on photography, species identification, and social media promotion of local biodiversity. Evaluation using pre-test and post-tests showed an increase in participants’ photography knowledge (mean score 7.57 to 8.71), indicating improved awareness and skills in documenting biodiversity. The program successfully enhanced local capacity to promote sustainable ecotourism while fostering conservation ethics.